Application of Athletic Movement Tests that Predict Injury Risk in a Military Population: Development of Normative Data. Issue 10 (1st October 2016) - Teyhen, Deydre S.; Shaffer, Scott W.; Butler, Robert J.; Goffar, Stephen L.; Kiesel, Kyle B.; Rhon, Daniel I.; Boyles, Robert E.; McMillian, Daniel J.; Williamson, Jared N.; Plisky, Phillip J.
ABSTRACT: Performance on movement tests helps to predict injury risk in a variety of physically active populations. Understanding baseline measures for normal is an important first step. Objectives: Determine differences in physical performance assessments and describe normative values for these tests based on military unit type. Methods: Assessment of power, balance, mobility, motor control, and performance on the Army Physical Fitness Test were assessed in a cohort of 1, 466 soldiers. Analysis of variance was performed to compare the results based on military unit type (Rangers, Combat, Combat Service, and Combat Service Support) and analysis of covariance was performed to determine the influence of age and gender. Results: Rangers performed the best on all performance and fitness measures ( p < 0.05). Combat soldiers performed better than Combat Service and Service Support soldiers on several physical performance tests and the Army Physical Fitness Test ( p < 0.05). Performance in Combat Service and Service Support soldiers was equivalent on most measures ( p < 0.05). Conclusions: Functional performance and level of fitness varied significantly by military unit type. Understanding these differences will provide a foundation for future injury prediction and prevention strategies.